Estimating the Impact of Labor Taxes on Employment and the Balances of the Social Insurance Funds in Turkey - World Bank (World Bank, Washington, DC, 2017)
High labor tax wedges and slow formal employment growth have combined to make labor tax reform an important economic policy issue in Turkey. This synthesis report presents the results of a series of empirical studies of the impact of a labor tax reform. The analysis was undertaken before the social contribution reforms that were introduced as part of the 2008 employment package. Using data from firms, households, and social insurance files, the research finds that employment does respond to changes in labor costs at levels that are comparable to those found in other middle-income and Organization for Economic Co-operation and Development (OECD) countries. The results show that reducing labor costs could significantly boost registered employment. However, the actual effect of lower taxes on employment would be diluted because a significant portion of the reduced tax will be captured by workers through higher wages rather than by employers through lower labor costs. As a result, tax cuts targeted towards low-wage labor would be more cost-effective than across-the-board reductions. To achieve overall fiscal neutrality, compensating additional revenues from other sources or reduced expenditures will be needed to accompany lower contribution rates.